FORMULATION DEVELOPMENT AND EVALUATION OF BILAYER TABLETS OF PITABASTATIN - Khan, Shahnvaz; Sahil, Sana; Budholiya, Prabhakar (Journal of Biomedical and Pharmaceutical Research, 2021)
The objective of the present study was to develop bi-layer tablets of Pitabastatin, a highly potent antihyperlipidemic drug with short half-life, that are characterized by initial burst drug release in the stomach and comply with the release requirements of sustained-release products. Each of the proposed bi-layer tablets is composed of an immediate-release layer and a sustained-release layer, anticipating rapid drug release that starts in the stomach to rapidly alleviate the symptoms and continues in the intestine. Immediate release layer prepared by using dry granulation method for immediate release of drug, roll compaction of drug with sodium citrate which act as buffering agent and create basic micro-environmental pH inside the tablets favorable to drug release in acidic conditions. Sustained release layer formulated by using HPMC as release retardant, two grades of HPMC that are HPMC K4M and HPMC K100M used to get sustained release profile for 24 hr. various trial batches are taken to get desired release profile. All the prepared bilayer tablets showed acceptable physical properties before and after storage. Keyword: Bilayer tablets, Antihyperlipidemic drug, Pitabastatin